2001
DOI: 10.1029/2000gl012611
|View full text |Cite
|
Sign up to set email alerts
|

New constraints on Laurentide postglacial rebound from absolute gravity measurements

Abstract: Abstract. Repeated absolute gravity measurements have been made over a period of several years at six sites along a 3000 kmlong, mid-continental, North American profile from the coast of Hudson Bay southward to Iowa. With the exception of the southern-most site, the observed rates of change of gravity are significantly higher than rates predicted by current models, such as ICE-3G and a laterally homogeneous, standard Earth. The observed gravity change rates suggest significant modifications, such as a 2 to 3-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 19 publications
4
66
1
Order By: Relevance
“…For the optimum viscosity profile, this modification leaves the predictions of the late-and post-glacial RSL heights nearly unchanged, whereas the predicted rates of RSL-height change, topographic-height change and gravity change are enhanced by ≃ 5%. This increase can be compensated by a slight reduction of the lower-mantle viscosity by a factor of < 2 -a result in agreement with that obtained by Lambert et al (2001).…”
Section: New Estimate Based On Joint Inversionsupporting
confidence: 80%
See 2 more Smart Citations
“…For the optimum viscosity profile, this modification leaves the predictions of the late-and post-glacial RSL heights nearly unchanged, whereas the predicted rates of RSL-height change, topographic-height change and gravity change are enhanced by ≃ 5%. This increase can be compensated by a slight reduction of the lower-mantle viscosity by a factor of < 2 -a result in agreement with that obtained by Lambert et al (2001).…”
Section: New Estimate Based On Joint Inversionsupporting
confidence: 80%
“…This is significantly higher than predicted using ice model ICE-3G and a 'standard' earth model (Tushingham and Peltier, 1991). Lambert et al (2001) noted that the discrepancy can be avoided either by an increase of the lower-mantle viscosity by a factor of ∼2 or by a 50% increase in thickness of ICE-3G on the Canadian Shield west of Lake Superior. analysed data from four locations in Canada and the northern USA based on at least three years of continuous GPS observations and at least two absolute-gravimetry campaigns.…”
Section: Previous Analysesmentioning
confidence: 69%
See 1 more Smart Citation
“…Lambert et al (1996) gives an overview of the capability of absolute gravity measurements in determining the temporal variations in the Earth's gravity field. In Lambert et al (2001), the gravimetric results for the research of the Laurentide postglacial rebound in Canada are described. Mäkinen et al (2007) compares observed gravity changes in Antarctica with modelled predictions of the glacial isostatic adjustment as well as of the glacier mass balance.…”
Section: Absolute Gravimetrymentioning
confidence: 99%
“…This ratio is a function of the wavelength, the rheology and the history of the deformed layers and depends on the position of the load and on geodynamic process, so it depends on whether specific sites are located inside formerly glaciated areas, or peripheral, or in between; on how wide the respective ice sheet was, and whether there is elastic response due to contemporary ice changes, earthquakes or tectonic processes [Rundle, 1978;Wahr et [23] The ratio ( _ g/_ z) has not yet been experimentally determined with the required accuracy to allow discrimination between the modeled values [Ekman and Mäkinen, 1996;Lambert et al, 2001;Mazzotti et al, 2007]. For comparison, the observed gravity rates of change, converted into vertical velocities using the published plausible ratios are also shown in Figure 3b by the black (_ z observed = − _ g observed /1.0) and blue (_ z observed = − _ g observed /2.6) symbols, providing upper and lower values for the possible vertical velocities inferred from our AG measurements.…”
Section: Gravity Rates Of Change Versus Vertical Velocitiesmentioning
confidence: 99%